Phycocyanin functionalized single-walled carbon nanohorns hybrid for near-infrared light-mediated cancer phototheranostics. (March 2019) - Lin, Zhaoxing; Jiang, Bang-Ping; Liang, Jinzhe; Wen, Changchun; Shen, Xing-Can
Abstract: Application of carbon nanomaterials to near-infrared light-mediated phototherapy has attracted great interest. However, their practical use in biological systems is severely limited by their poor water dispersibility, inevitable adsorption of plasma proteins, and their single therapeutic function. Herein, we prepared a phycocyanin (PC)-functionalized single-walled carbon nanohorns (PC@SWNHs) hybrid, where PC is used to preform a protein corona around the SWNHs through non-covalent interface interactions. In the PC@SWNHs, the preformed PC corona effectively improves the water dispersibility of the SWNHs and protects them from plasma protein adsorption. In addition, the excellent photodynamic activity of PC overcomes the inability of SWNHs to generate reactive oxygen species. The SWNHs not only give the hybrid a photothermal therapy (PTT) function, but they also enhance the photostability of PC. These characteristics of the PC@SWNHs are confirmed by in vitro and in vivo experiments, where synergistic photodynamic therapy (PDT)/PTT growth inhibition of tumors is achieved. The PC@SWNHs also act as a photoacoustic/thermal imaging agent to visualize the in vivo treatment process. Hence, this work not only paves the way to use the complementarity between SWNHs and proteins for multifunctional cancer theranostics, but it also allows for a better understanding of bio–nano interface interactions between them. Graphical abstract: